2021
DOI: 10.23937/2474-1353/1510133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High Risk Pregnant Women Who Attend Antenatal Care and Associated Factors in Jimma Medical Center, Jimma Town, South Western Ethiopia

Abstract: Background: Around 303,000 women and adolescent girls pass on from pregnancy and childbirth-related complications in 2015 and 99% of these deaths occur in developing countries. That same year, 2.6 million babies were stillborn. Almost all of the maternal deaths (99%), child deaths (98%), Sixty percent of the stillbirths (1.46 million) occurred during the antepartum period and mainly due to untreated maternal infection, hypertension, and poor fetal growth and occurred in low-and middle-income countries. These m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The prevalence of high risk pregnancy among 350 deliveries during the study period was 91 (26%) in our study which is consistent with previous studies done in Hyderabad, India (2020) and South Western Ethiopia (2021) where prevalence of high risk pregnancy was 25.9% and 26.43% respectively. 3,4 This study is not in agreement with the studies done in Nepal at Shree Birendra military hospital (2017),and Koshi Hospital in the Morang district (2020), where low prevalence of high risk pregnancy was identified 15.81% and 14.4% respectively. 5,6 Similarly, studies conducted in India at Puducherry (2019) and Haryana (2020) showed low prevalence of 18.3% and 12.73% respectively.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The prevalence of high risk pregnancy among 350 deliveries during the study period was 91 (26%) in our study which is consistent with previous studies done in Hyderabad, India (2020) and South Western Ethiopia (2021) where prevalence of high risk pregnancy was 25.9% and 26.43% respectively. 3,4 This study is not in agreement with the studies done in Nepal at Shree Birendra military hospital (2017),and Koshi Hospital in the Morang district (2020), where low prevalence of high risk pregnancy was identified 15.81% and 14.4% respectively. 5,6 Similarly, studies conducted in India at Puducherry (2019) and Haryana (2020) showed low prevalence of 18.3% and 12.73% respectively.…”
Section: Discussionmentioning
confidence: 54%
“…3 While in a hospital based study in South Western Ethiopia (2021), the leading risk factor identified in the index pregnancies were hypertension in 40 (12.5%) cases, anemia in 15 (4.8%) cases, 12 (3.8%) had Diabetes Mellitus, 9 (2.87%) had Antepartum Hemorrhage, 7 (2.2%) had malpresentation. 4 Similarly study conducted in Shree Birendra military hospital, Nepal (2017), reported previous lower segment cesarean section as the most common identified high risk pregnancy in 34 (5.43%) cases followed by young primi gravida (3.19%), and breech (2.23%). 5 In contrast, study done in Pakistan (2017) found that among the systemic diseases, anemia (37%) was the most common risk factor followed by hypertension (20%).…”
Section: Discussionmentioning
confidence: 95%
“…According to our study, the country's overall prevalence of HRP was 49.4%, which is higher than that of adjacent countries like Nepal (14.4%) [20], Bangladesh (41.5%) [21], China (24.5%) [22], as well as other low-middle income countries like Ethiopia (26.4%) [23] and the Democratic Republic of Congo (33.1%) [24]. Among all pregnancies, nearly one-third of Indian pregnant women had at least one high-risk factor and sixteen percent of women had multiple-high risks.…”
Section: Discussionmentioning
confidence: 61%
“…This aligns with a previous study reporting a HRP prevalence of 54.5–65.0% in China across four cities in 2019 [ 7 ], and is similar to findings from other settings such as Iran (75%) [ 36 ] and Korea (71.7%) [ 37 ]. However, this observed prevalence is higher than that of countries like India (49.4%) [ 18 ], Nigeria (21.5%) [ 38 ], and Ethiopia (26.4%) [ 39 ]. These variations may partly be explained by differences in the definitions and screening frameworks of HRP; diagnostic accuracy; the quality of antenatal, intranatal, and postnatal interventions; and socioeconomic differences across different regions.…”
Section: Discussionmentioning
confidence: 84%